Challenges Faced by ELT Teachers in Adopting ChatGPT as an Instructional Tool - Maspufah; Afriyeni, Yeni; Zuriati, Diana; Masbiran, Gunaldi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Generative artificial intelligence (AI) ChatGPT hold remarkable opportunities for enhancing language teaching and learning. However, integrating ChatGPT into classroom activity created challenges for teachers such as lack familiarity with the technology, difficulty to differ AI or students’ generated work, weaken students’ creativity and critical thinking. The purpose of the research was to find out challenges faced by ELT teachers in adopting ChatGPT as an instructional tool. This was descriptive qualitative research. It was conducted to thirteen private senior high school teachers in Riau. The sample was taken by purposive sampling technique. The data were collected through semi-structured interviews conducted over Zoom and WhatsApp voice calls. The data were analysed thematically by applying Braun and Clarke’s theory. The finding indicated that ChatGPT adoption among ELT teachers remains constrained by pedagogical uncertainty, ethical concerns, limited technical competence, and inadequate institutional support. Teachers continue to struggle with aligning AI tools to learning objectives, ensuring academic integrity, and verifying the accuracy of AI-generated content, while also navigating unclear policies and unstable technological infrastructure. In conclusion, language teachers faced many challenging in adopting ChatGPT in their teaching. Therefore, it was suggested to educational institution who willing to adopt it into their instruction needed to facilitate workshop or training on AI, especially ChatGPT and digital literacy for their teachers.